2010
DOI: 10.1111/j.1095-8312.2010.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Population and species boundaries in the South American subterranean rodent Ctenomys in a dynamic environment

Abstract: Subterranean rodents of the genus Ctenomys are an interesting system to assess the effects of habitat instability on the genetic structure of populations. The perrensi group is a complex of three species (C. roigi, C. perrensi and C. dorbignyi) and several forms of uncertain taxonomic status, distributed in the vicinity of the Iberá wetland in Argentina. Because of limited availability of suitable dry habitat, Ctenomys populations are distributed patchily around a vast mosaic of marshes, swamps and lagoons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 71 publications
8
49
0
4
Order By: Relevance
“…This population shows a secondary affinity to the Ctenomys perrensi complex, being basal to the clade 2 in the mtDNA phylo geny and, although it forms an exclusive SSR cluster (L), it is included into a hierarchic cluster together with San Roque, Goya and Chavarría (Table 1). In fact, when members of San Joaquín de Miraflores (Entre Ríos) are included in the analysis, Paraje Sarandicito falls into a SSR cluster with this population (Mirol et al 2010). However, as stated above, San Joaquín de Miraflores falls within a clade which also includes the C. pearsoni complex in the cyt-b based phylogeny (Figure 3) and hence belongs to a different lineage.…”
Section: Sarandicitomentioning
confidence: 91%
See 3 more Smart Citations
“…This population shows a secondary affinity to the Ctenomys perrensi complex, being basal to the clade 2 in the mtDNA phylo geny and, although it forms an exclusive SSR cluster (L), it is included into a hierarchic cluster together with San Roque, Goya and Chavarría (Table 1). In fact, when members of San Joaquín de Miraflores (Entre Ríos) are included in the analysis, Paraje Sarandicito falls into a SSR cluster with this population (Mirol et al 2010). However, as stated above, San Joaquín de Miraflores falls within a clade which also includes the C. pearsoni complex in the cyt-b based phylogeny (Figure 3) and hence belongs to a different lineage.…”
Section: Sarandicitomentioning
confidence: 91%
“…Karyotypical information was then published by Ortells et al (1990) who found that Mbarigüí and Paraje Sarandicito had undistinguishable 2n = 70 FN = 84 karyotypes (Table 1). Hence, these two disjunct nucleuses, although they are 350 km away, maintained their adscription to Ctenomys dorbignyi and were identified as relicts (Mirol et al 2010, Gómez Fernández et al 2012, mtDNA phylogenetic clades (Caraballo et al 2012) Argüelles et al (2001) ascribed to this species a third karyotypically related group of populations from the localities of Paso Vera and San Joaquín de Miraflores, at the Entre Ríos Province. Taking these three nucleuses into consideration C. dorbignyi was considered Near Threatened in the IUCN Red List (Bidau et al 2008b).…”
Section: Ctenomys Dorbignyimentioning
confidence: 93%
See 2 more Smart Citations
“…Эта классификация была основана главным образом на анализе морфологических признаков, таких как особен-ности морфологии черепа, окраски меха и размера тела. Со временем для классификации стали использовать особенности кариотипов (Reig, Kiblisky, 1969), морфо-логию сперматозоидов (Feito, Gallardo, 1982), частоты аллозимных локусов (Sage et al, 1986) и молекулярных маркеров (Lessa, Cook, 1998;Mascheretti et al, 2000;Giménez et al, 2002;Castillo et al, 2005;Mirol et al, 2010;Parada et al, 2011).…”
Section: эволюционная история и современная дивергенция рода Ctenomysunclassified